Penerapan Hipnosis Lima Jari Terhadap Ansietas Pada Pasien Hipertensi Di Wilayah Puskesmas Cikoneng Kabupaten Ciamis - Asep Riyana; Rahmat, Salsabila (Jurnal Kesehatan Mahardika, 2023)
The high mortality due to hypertension and various possible complications due to hypertension can make people with hypertension not only have physiological but also psychological diseases such as anxiety. Hypertension sufferers who experience anxiety will show mental symptoms in the body such as stuttering, panic, fear. Mental symptoms in other anxiety vary, such as dizziness or lightheadedness, difficulty breathing, lack of fluids, excess watery bowel movements, heart palpitations. The prevalence of hypertension varies greatly in each region. Based on data taken regarding the summary of reports of the 10 most common diseases at the UPTD Cikoneng Health Center in 2021, hypertension is in third place with a total of 656 people. The purpose of this study was to describe the application of five finger hypnosis to people with anxiety. The process of providing nursing care was carried out for three days, starting from April 4 to April 9 2022. The problem experienced by the client was the level of anxiety and hypertension experienced by Mrs.E and Mrs.Y. the conclusion that there is an influence in the application of five finger hypnosis therapy on anxiety in hypertensive patients.